Goal Programming Model for Tutor Scheduling - Nikmah, Herlin; Sutarman,; Darnius, Open (Journal of Research in Mathematics Trends and Technology, 2021)
This article presents goal programming model for tutor scheduling. Goal programming is the development of linear programming which has multiple objectives. Goal programming minimizes the deviation among the the desired level of goals and the actual achievement, which is achieved by changing inequality into equality by including positive and negative deviation variables accomplished by converting inequalities into equalities by including positive and negative deviation variables that allow the achievement below or above each goal. The results obtained from this model provide the optimal solutions where all objectives are achieved. This model also aims to achieve harmony and fairness between tutors and institutional management.